The marine macroalgae of Cabo Verde archipelago : an updated checklist - Gabriel, Daniela (2020)
An updated list of the names of the marine macroalgae of Cabo Verde, an archipelago of ten volcanic islands in the central Atlantic Ocean, is presented based on existing reports, and includes the addition of 36 species. The checklist comprises a total of 372 species names, of which 68 are brown algae (Ochrophyta), 238 are red algae (Rhodophyta) and 66 green algae (Chlorophyta). New distribution records reveal the existence of 10 putative endemic species for Cabo Verde islands, nine species that are geographically restricted to the Macaronesia, five species that are restricted to Cabo Verde islands and the nearby Tropical Western African coast, and five species known to occur only in the Maraconesian Islands and Tropical West Africa. Two species, previously considered invalid names, are here validly published as Colaconema naumannii comb. nov. and Sebdenia canariensis sp. nov.